2020
DOI: 10.21203/rs.3.rs-48469/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression of Long-Chain Noncoding RNA GAS5 in Osteoarthritis And Its Effect on Apoptosis And Autophagy of Osteoarthritis Chondrocytes

Abstract: Objective: To investigate the expression of long chain non-coding RNA GAS5 in osteoarthritis(OA) and the effect on autophagy and apoptosis of chondrocytes. Method: OA rat model was constructed and the expressions of GAS5 in articular cartilage tissues at 4 weeks(early OA) and 12 weeks(late OA) after modeling were detected. The chondrocytes of OA rat were isolated, cultured and transfected with si-GAS5 to silence the GAS5. Then the change of apoptosis and autophagy levels of OA chondrocytes were detected. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Studies have shown that lncRNA GAS5 is highly expressed in OA cartilage and increases with the progress of OA. GAS5 inhibits autophagy and promotes apoptosis of chondrocytes, which may be related to miR-34a / Bcl-2 axis or mTOR [35,36]. Similarly, LINC02288 expression was signi cantly up-regulated in OA rat model.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that lncRNA GAS5 is highly expressed in OA cartilage and increases with the progress of OA. GAS5 inhibits autophagy and promotes apoptosis of chondrocytes, which may be related to miR-34a / Bcl-2 axis or mTOR [35,36]. Similarly, LINC02288 expression was signi cantly up-regulated in OA rat model.…”
Section: Discussionmentioning
confidence: 95%
“…LncRNA GAS5 expression is up regulated in OA cartilage tissues. Silence of GAS5 increases the autophagy ability and decreases the apoptosis rate by sponging miR-144 [ 25 ]. In addition, the increased expression of lncRNA PVT1 in diabetic OA cartilage is also associated with Mankin score and reduced expression of type II collagen by negatively interacting with miR-146a, increasing the productions of inflammatory cytokines, and activating TGFβ/SMAD4 signaling pathway [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA GAS5 expression is up regulated in OA cartilage tissues. Silence of GAS5 increases the autophagy ability and decreases the apoptosis rate by sponging miR-144 ( Ji et al, 2021 ). Similarly, our study also demonstrated that GAS5 expression was significantly increased by mechanical stimulation in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%